Workers Are More Productive in Large Firms - Idson, Todd L; Oi, Walter Y (American Economic Review, 1999)
Wages are positively related to firm size. This relation was discovered by Henry L. Moore (1911) and later confirmed by, among others, Charles Brown and James Medoff (1989). The wage premium associated with working at a larger firm or plant is ubiquitous, but its magnitude varies across countries and over time. The reason for a size-related wage premium is harder to pin down. Paying supernormal wages to deter shirking, thereby saving monitoring costs, seems plausible, but a closer examination has led us to reject this explanation (Oi and Idson, 1999). At a big firm, the workplace is safer, and fringes are superior, so that these factors cannot be the source of a positive premium. It must be something else such as work effort. The theory that we advance is that employees at larger firms are more productive and hence command higher wages in a competitive labor market. The shape of the size–wage relation depends on technology, worker preferences, and working conditions other than size. It will change over time and across occupations.